2017
DOI: 10.1002/adma.201703393
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanohybrid Based on Porous Silicon Nanoparticles, Gold Nanoparticles, and Acetalated Dextran for Liver Regeneration and Acute Liver Failure Theranostics

Abstract: Herein, a novel nanohybrid based on porous silicon, gold nanoparticles (Au NPs), and acetalated dextran (DPSi/DAu@AcDEX) is reported to encapsulate and deliver one drug and increase the computer tomography (CT) signal for acute-liver-failure (ALF) theranostics. A microfluidic-assisted method is used to co-encapsulate different NPs in a single step. By alternating the surface properties of different NPs and by modulating the composition of the organic phase, both PSi and Au NPs are effectively encapsulated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 44 publications
2
69
0
1
Order By: Relevance
“…Copyright 2017, American Chemical Society. (e) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Microfluidic Production Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2017, American Chemical Society. (e) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Microfluidic Production Of Nanoparticlesmentioning
confidence: 99%
“…In addition to form single core/shell structures, achieving a multihierarchical, multifunctional nanosystem, simultaneous coencapsulation of two or more types of NPs with altered physiochemical properties within one matrix, is also in great demand. Liu et al demonstrated the simultaneous coencapsulation of PSi NPs (≈200 nm) and gold (Au) nanoparticles (<5 nm) into a single polymeric matrix, and further applied it for acute liver failure theranostic therapy (Figure e) . The application of PSi NPs enhanced the loading degree of a hydrophobic drug (2,4‐((5,10‐dimethyl‐6‐oxo‐6,10‐dihydro‐5H‐pyrimido[5,4‐ b ] thieno[3,2‐e][1,4]diazepin‐2‐yl)amino)benzenesulfonamide) from 0.04% to 7.8%, and coresidence of Au NPs endowed the system with the capability to function as a contrasting agent for computed tomography (CT) imaging.…”
Section: Microfluidic Production Of Nanoparticlesmentioning
confidence: 99%
“…On the contrary, unlike the dissipation function of hydrophobic association in hydrogel, strong and stable hydrophobic association was proposed in the present study to restrict the hydrophilic swollen network, so to endow the hydrogels with high strength and elastic behavior. In this regard, the hydrophilic nature of dextran make it available in hydrogels construction, exhibiting remarkable biological and physi‐chemical properties . Poly (ε‐caprolactone) (PCL), possesses biocompatibility, was used biomaterials in several studies for its well performed mechanical properties .…”
Section: Discussionmentioning
confidence: 99%
“…XMU‐MP‐1 was dissolved in DMSO and injected intraperitoneally at a dose of 1 mg·kg −1 BW, given every 2 days. The dosing regimen was based on the pharmacokinetics data of XMU‐MP‐1 in a rodent model (Fan et al, ) and functional assays showing the effects of XMU‐MP‐1 injection (1 mg·kg −1 ) in reducing MOB1 phosphorylation in mice (Fan et al, ; Liu et al, ). XMU‐MP‐1 treatment started at 21 days post‐surgery for further 10 days.…”
Section: Methodsmentioning
confidence: 99%